Adult limbal neurosphere cells: a potential autologous cell resource for retinal cell generation. - Xiaoli Chen; Heather Thomson; Jessica Cooke; Jennifer Scott; Parwez Hossain; Andrew Lotery (PLoS ONE)
The Corneal limbus is a readily accessible region at the front of the eye, separating the cornea and sclera. Neural colonies (neurospheres) can be generated from adult corneal limbus in vitro. We have previously shown that these neurospheres originate from neural crest stem/progenitor cells and that they can differentiate into functional neurons in vitro. The aim of this study was to investigate whether mouse and human limbal neurosphere cells (LNS) could differentiate towards a retinal lineage both in vivo and in vitro following exposure to a developing retinal microenvironment. In this article we show that LNS can be generated from adult mice and aged humans (up to 97 years) using a serum free culture assay. Following culture with developing mouse retinal cells, we detected retinal progenitor cell markers, mature retinal/neuronal markers and sensory cilia in the majority of mouse LNS experiments. After transplantation into the sub-retinal space of neonatal mice, mouse LNS cells expressed photoreceptor specific markers, but no incorporation into host retinal tissue was seen. Human LNS cells also expressed retinal progenitor markers at the transcription level but mature retinal markers were not observed in vitro or in vivo. This data highlights that mouse corneal limbal stromal progenitor cells can transdifferentiate towards a retinal lineage. Complete differentiation is likely to require more comprehensive regulation; however, the accessibility and plasticity of LNS makes them an attractive cell resource for future study and ultimately therapeutic application.